Analisis Faktor-Faktor Yang Memotivasi Mahasiswa Berwirausaha - Hendrik Nurhantoro; Subagijo Subagijo (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
Being entrepreneurial is one of a very promising alternative for students who will be faced with the difficulty of finding a job. To know the spirit of entrepreneurship among the students, then the thing to know is the factors that influence students motivation to entrepreneurship. Population used in this research is S1 Accounting and Management STIE Nganjuk students. The number of samples in this study is 74 peoples. In this research is done by regression method, where to reach the first goal is to analyze the influence of independent variables that is self-success in entrepreneurship, tolerance of risk, and desire to feel freedom in working on the dependent variable is entrepreneurship desire. The results of this study indicate that all independent variables, namely self-success in entrepreneurship, tolerance of risk, and the desire to feel freedom in work have a positive and significant impact on student motivation to entrepreneurship.